Axillary Plexus Block for Anesthesia Management in Patients with Acute Compartment Syndrome after Primary Percutaneous Coronary Intervention (PCI) Transradial Approach: A Case Report - Renaldi; I Made Gede Widnyana; Otniel Adrians Labobar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Acute compartment syndrome is a rare complication of the percutaneous Coronary Intervention (PCI) transradial approach but it is very hand-threatening. Treatment for acute compartment syndrome is emergent fasciotomy of the affected compartments to reduce intracompartmental pressure. Axillary plexus block is an excellent choice of anesthesia technique for elbow, forearm, and hand surgery. Case presentation: An 80-year-old, 60 kg, 168 cm man was consulted to our department with a painful swelling on his right upper arm and hand that began three hours after a primary PCI procedure. Previously, the patient had a history of hypertension and diabetes mellitus. The supporting examination results were notable for anemia (Hemoglobin 7,5 g/dL), thrombocytopenia (78 x103/uL), elevated hemostasis function (International Normalized Ratio 1.43), and high blood sugar (360 mg/dL) from echocardiography results anteroseptal and lateral hypokinetic. Before we did block, the patient was given ketamine 10 mcg IV and fentanyl 25 mcg IV for sedation. Axillary plexus block, as a type of regional anesthesia under ultrasound guidance, is a reliable substitute for general anesthesia in high-risk patients, and we do it with a dose of 20 ml of solution (50 mg (10 ml) isobaric bupivacaine 0.5% + 200 mg lidocaine 2% diluted with 20 ml normal saline). During the surgery, the patient was hemodynamically stable. After the operation, the patient was readmitted to the intensive cardiac care unit (ICCU). Conclusion: Axillary plexus block can be an alternative to general anesthesia in patients who will undergo fasciotomy surgery after percutaneous coronary intervention transradial approach with stable hemodynamics during surgery and well-controlled pain after the surgery.